2016
DOI: 10.1097/md.0000000000003068
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Computerized Adaptive Short-Form Quality of Life Questionnaire Developed and Validated for Multiple Sclerosis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 52 publications
2
9
1
Order By: Relevance
“…In this study, women had lower QoL scores than men, which is consistent with findings from one previous study. 42 Older age was significantly associated with worse scores, which is also consistent with previous findings. 42 Higher educational level or being in a couple was associated with higher QoL levels, as previously reported in similar cross-sectional studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, women had lower QoL scores than men, which is consistent with findings from one previous study. 42 Older age was significantly associated with worse scores, which is also consistent with previous findings. 42 Higher educational level or being in a couple was associated with higher QoL levels, as previously reported in similar cross-sectional studies.…”
Section: Discussionsupporting
confidence: 91%
“… 42 Older age was significantly associated with worse scores, which is also consistent with previous findings. 42 Higher educational level or being in a couple was associated with higher QoL levels, as previously reported in similar cross-sectional studies. 26 , 43 As expected, the DRT-based CAT score was more correlated with the dimension scores of the SF-36, with the MusiQoL constituting the item bank.…”
Section: Discussionsupporting
confidence: 91%
“…The lower the SEM, the higher the CAT reliability 99. To achieve satisfactory reliability (≥0.70), the SEM must be less than 0.55 100…”
Section: Methodsmentioning
confidence: 99%
“…Summarizing the available literature illustrating the feasibility and advantages of using MCAT in the field of health measurement, it can be observed that—although each of these studies made important contributions to the field—each of them had serious limitations when it comes to demonstrating the incremental value of MCAT over using separate UCATs. Some articles focused only on dichotomous data ( Allen et al, 2008 ; Haley et al, 2006 ), which is atypical for health measurement applications; other studies used very short item banks based on existing instruments not specifically developed for computerized adaptive testing ( Michel et al, 2016 ; Petersen et al, 2006 ), while the study by Bass and colleagues had a relatively low maximum test length and was restricted to two dimensions ( Bass et al, 2015 ). Nikolaus and colleagues advanced the field by studying the working mechanism of the MCAT they had developed to measure fatigue in patients with rheumatoid arthritis ( Nikolaus et al, 2015 ), as well as patient acceptance ( Nikolaus et al, 2014 ); they did not, however, explicitly compare MCAT with UCAT conditions.…”
Section: Introductionmentioning
confidence: 99%